Summary-Lamb feeding experiments - Cox, R.F.; Sloan, L.H. (Kansas Agricultural Experiment Station, 2012)
A number of years of lamb feeding experimental work involving grain comparisons, roughage comparisons, roughage comparisons and proportions of concentrates to roughage, conducted at the Kansas Agricultural Experiment Station are reported in detail in Table I, II and III. Some other phases of experimental work conducted at the Kansas station in recent years are summarized within.
Keywords: Lamb; Feeding; Acre value; Sugar beet; Wheat pasture